Development of two-photon fluorescence probe for detecting cyclooxygenase-2 level in human colorectal cancer tissue - Park, Sang Jun; Cho, Myoung Ki; Lee, Dong Joon; Song, Deuk Hwa; Lim, Chang Su; Noh, Choong Kyun; Lee, Dong Min; Choi, Kyeong Sook; Shin, Sung Jae; Kim, Hwan Myung (Sensors and Actuators, B: Chemical, 2021)
Cyclooxygenase-2 is overexpressed in all stages of cancers and thus serves as an attractive biomarker for early cancer diagnosis. In this study, we report a two-photon probe (SCX) for cyclooxygenase-2 which can reflect the intracellular enzyme level and distinguish between cancerous and normal tissue in colorectal cancer patients. SCX is based on a novel two-photon fluorophore (PBT) possessing phenanthrene donor and benzothiazole acceptor, and indomethacin as a COX-2 targeting unit. The in vitro and cell imaging studies revealed that SCX could distinguish the COX-2 expression levels in cancerous and normal cells. Furthermore, for the first time, normal and cancerous tissues could clearly be distinguished in human biopsy samples by using a COX-2 responsible two-photon probe.
Keywords: Cancerous tissues; Colorectal cancer; Cyclooxygenase 2; Expression levels; Intracellular enzyme; Two photon fluorescence; Two-photon fluorophores; Two-photon probes; Colorectal cancer; Cyclooxygenase-2; Human tissue; Two-photon microscopy; Two-photon probe